Neurological Complications of Cardiac Procedures - Hrdlicka, Courtney M.; Wang, Jeffrey; Selim, Magdy (Seminars in Neurology, 2021)
Neurological complications after cardiac surgery and percutaneous cardiac interventions are not uncommon. These include periprocedural stroke, postoperative cognitive dysfunction after cardiac surgery, contrast-induced encephalopathy after percutaneous interventions, and seizures. In this article, we review the incidence, pathophysiology, diagnosis, and management of these complications. Improved understanding of these complications could lead to their prevention, faster detection, and facilitation of diagnostic workup and appropriate treatment.
Keywords: stroke; coronary artery bypass graft; percutaneous coronary intervention; transcatheter aortic valve implantation; perioperative complication